Rhizosphere Microbiome Restructuring Enhances Nutrient Use Efficiency and Crop Yield: Mechanisms, Innovations, and Future Perspectives - Lahar Jyoti Bordoloi; Chakpram Birendrajit; Mahua Banerjee; Abhijit Debnath; Ratan Das (Public Health, 2026)
The rhizosphere microbiome plays a crucial role in regulating plant health, nutrient acquisition, and overall agricultural productivity. Recent advances in microbial ecology and biotechnology have highlighted the importance of restructuring rhizosphere microbial communities to enhance nutrient use efficiency (NUE) and crop yield. This review synthesizes current knowledge on the mechanisms through which beneficial soil microorganisms, including plant growth-promoting rhizobacteria (PGPR), mycorrhizal fungi, and endophytes, influence nutrient cycling, root architecture, and stress resilience. Key mechanisms such as biological nitrogen fixation, phosphorus solubilization, phytohormone production, and microbial signaling are discussed in detail. Emerging innovations, including microbiome engineering, biofertilizers, and precision agriculture approaches, are evaluated for their potential to sustainably improve crop productivity under changing climatic conditions. Additionally, the role of multi-omics tools in understanding plant–microbe interactions and guiding targeted microbiome interventions is emphasized. Despite promising advancements, challenges such as field variability, microbial survival, and scalability remain significant barriers to widespread adoption. Future perspectives focus on integrating microbiome-based strategies with conventional agronomic practices to achieve sustainable intensification of agriculture while ensuring environmental and public health safety. This review underscores the critical importance of rhizosphere microbiome restructuring as a viable approach to improving nutrient efficiency and ensuring global food security.Rhizosphere microbiome;